Efforts to Handle the Increase in Togel Gambling Users During a Pandemic Judging from Law No. 7 of 1974 - Adi Sarlup (IHSA Institute, 2022)
Lottery gambling is a crime that is troubling the community and the impact is so large on the survival of the community. The purpose of this research 1. How is the police in the process of handling lottery gambling in the city of Ambon. 2. What are the factors that influence the increase in lottery gambling in Ambon City. 3. What is the role of the police in dealing with lottery gambling in Ambon City? This study uses a qualitative approach and data collection techniques in this study using observation, interviews and using qualitative descriptive data analysis techniques. The results of this study indicate that, the efforts to handle lottery gambling in Ambon City by the police have been carried out well, but the approach to the community has not been maximized.